Making managerial planning more effective - Allen, Louis A. 4 0 16; 5 (New York : McGraw-Hill Company, 1982)
Tells how to use plans to streamline, fine-tune, and maximize production.
Includes bibliographical references and index.
Young Adult.
Keywords: 2 -- 0; 6; Corporate planning.;Management.; 20; 2